Morphological characterization of nevi on the caruncle conjunctiva under in vivo confocal microscopy - Cai, Jianhao; Xu, Cangeng; Ng, Tsz Kin; Li, Zeyi (Frontiers in Medicine, 2023)
Objective: To investigate the microscopic structure and characteristics of nevus on the conjunctiva of lacrimal caruncle by in vivo confocal microscopy. Methods: In total, 4 patients with nevus grown on the lacrimal caruncle conjunctiva were recruited. The morphological characteristics of the nevus on the lacrimal caruncle conjunctiva were evaluated by the in vivo confocal microscopy before excision surgery and compared with the histopathological analysis on the surgical specimens. Results:The nevi of the 4 patients were all located at the conjunctiva of the lacrimal caruncle, with a slightly nodular surface, mixed black and brown color, and clear boundary. Thenevi were round in shape and highly protruded on the surface of the lacrimal caruncle, with an average diameter of 4.5 ± 1.29 mm.Under the in vivo confocal microscopy, the pigmented nevus cells on the conjunctiva of the lacrimal caruncle clustered in nests with irregular boundaries. The cells were round or irregular, with clear cell boundaries, hyperreflective at the periphery, and low reflection in the center. Vascular crawling was observed in some regions.Histopathological analysis showed that the nevus cells were roughly equal in size and distributed in a nodular pattern. Melanin granules were observed in the cytoplasm. No atypia or mitotic figures of the cells were found. Conclusion: This study revealed that the microstructure of the nevus gorwn on the conjunctiva of the lacrimal caruncle can be identified by in vivo confocal microscopy.